Effects of furyl-dihydropyridine I on coronary collateral circulation in myocardial infarction of dogs - Jia Min-jiang; Chen Shi-liang; Liao Yu-lin; Liu De-qiang; Li Lan-sun; Zhao Nan-ping (Acta Pharmacologica Sinica, 2016)
Effects of furyl-dihydropyridine I (FDP-1) on collateral circulation were observed in ischemic myocardium of dogs. FDP-1 (200 micrograms.kg-1) of intracoronary injection increased collateral flow, reduced systemic artery resistance, and coronary systolic pressure in infarcted region and the area of infarction decreased from 28.9 +/- 1.3% to 15.3 +/- 1.2% (P < 0.01, n = 6). The results indicated that FDP-1 could improve coronary collateral circulation, increase collateral flow in ischemic region, decrease collateral flow in ischemic region, decrease myocardial oxygen demand, and protect myocardial ischemia.